PENGUKURAN USABILITY APLIKASI WEB MENGGUNAKAN SUS (SYSTEM USABILITY SCALE) DAN PENGUJIAN BLACK BOX PADA WEBSITE E-LEARNING (GEN-IT) KABUPATEN KATINGAN - Saputra, Septian Dwi; Parhusip, Jadiaman (Universitas Lampung, 2026)
The Gen-IT e-learning application plays a vital role in supportingthe digitalization of education in Katingan Regency, making it essential toevaluate both its technical quality and user experience. This study aims toassess the feasibility of the Gen-IT application using two approaches: blackbox testing and usability evaluation. The black box testing method was appliedto validate the core features from a technical perspective, while the SystemUsability Scale (SUS) method was used to evaluate user experience, involving17 respondents. The black box test results showed that 100% of the testscenarios were successfully executed without errors. Meanwhile, the usabilityevaluation achieved an average SUS score of 90.74, categorized as“Excellent” with a grade of “A”. These combined findings indicate that theGen-IT application not only demonstrates strong technical reliability but alsoprovides an outstanding user experience, making it an effective digitallearning tool.